Observation on prefrontal cortex activation in patients with Parkinson’s disease: a fNIRS study - Li, Yingqi; Hu, Tingting; Wang, Yingpeng; Wang, Jie; Qie, Shuyan; Wang, Congxiao (Frontiers in Aging Neuroscience, 2025)
BackgroundPatients with Parkinson’s disease (PD) commonly experience difficulties when performing a second task while walking. The mechanisms underlying dual-task walking deficits remain poorly understood. In previous studies the second tasks were often simplistic, typically comprising questions from standardized cognitive assessments. Additionally, existing fNIRS studies comparing PD patients and healthy controls have reported inconsistent findings, limiting our understanding of prefrontal cortex (PFC) contributions to cognitive-motor integration.MethodsForty-two healthy older adults (15 men and 27 women, age 59.97 ± 5.58 years) and fifty-eight patients with PD (25 men and 33 women, age 61.07 ± 7.56 years, Hoehn and Yahr stage 1∼3) were enrolled. The protocol consisted of three repetitions of these conditions: stationary marching and marching while two-digit arithmetic calculating. Researchers used fNIRS to measure PFC activation and changes in △HbO2 concentration during tasks execution.ResultsHealthy controls demonstrated task-dependent prefrontal modulation - selective activation (6/22 channels, p < 0.05) during single-task conditions contrasted with global prefrontal engagement (22/22 channels, p < 0.05) under dual-task demands. In contrast, PD patients showed widespread activation across all 22 channel regions during both single and dual tasks (p < 0.05). During task switching, healthy subjects experienced significant activation increases in 15/22 channel regions (p < 0.05), paralleled by significant rises in ΔHbO2 concentrations across five prefrontal regions (p < 0.05; Cohen’s d ranging from 0.43 to 0.82). Conversely, PD patients exhibited no significant difference in the activation of all 22 channel regions (p > 0.05), and no significant changes of ΔHbO2 concentrations across all regions between single and dual tasks (p > 0.05; Cohen’s d < 0.30).ConclusionFindings indicate that simple marching tasks underengage prefrontal resources in healthy individuals, whereas dual tasks engage greater prefrontal activation to meet heightened cognitive demands. In contrast, owing to disruptions in the cortico-basal ganglia-thalamocortical circuitry, PD patients exhibit a “ceiling effect” in PFC activation: increased task difficulty fails to elicit proportional activation, likely because single tasks already overtax prefrontal resources. This divergence in neural adaptability underscores core differences in cognitive-motor integration mechanisms between healthy individuals and PD patients, providing a basis for developing targeted dual-task interventions to enhance neural efficiency.